Dendrogeomorphic reconstruction of floods in a dynamic tropical river - Quesada Román, Adolfo (2020)
Tropical regions are frequently affected by intense floods causing substantial human and economic losses. A proper management of floods and the prevention of disasters is, however, often hampered by a generalized paucity of systematic discharge measurements, which in turn renders any assessment of the frequency and magnitude of extreme floods challenging or impossible. Here,we analyze the suitability of trees impacted by floods and their growth-ring records to provide insights into past flood activity and to allow estimation of their magnitude. Webase this exploratory study on the extreme floods triggered by the passage of tropical storm Nate on October 5, 2017 and investigate whether dendrogeomorphic approaches can be employed to date and quantify floods in the catchment of tropical Río General (Costa Rica). To this end, we sampled 91 trees showing scars in three river reaches and tested their potential to serve as paleostage indicators (PSI). High-resolution (0.5 m) digital surface and elevation models were then obtained with an Unmanned Aerial Vehicle to run a step-backwater hydraulic simulation aimed at defining flood peak discharge for which the mean squared errors between PSI heights and simulated water tables could be minimized. In a last analytical step, we investigated which hydraulic (i.e., Froude number, flow velocity) and fluvial landform characteristics explained deviations between scar heights and modeled water tables best by using a generalized linear model. Our analysis confirms that scarred trees can indeed be used for the reconstruction of past floods in tropical river systems and that the geomorphic position of trees will exert control on deviations between modeled water tables and scar height, with cut banks being most suited for scar-based flood reconstruction.